2021
DOI: 10.1155/2021/1735803
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Transformation of Protopanaxadiol Saponins in Human Intestinal Flora and Its Effect on Intestinal Flora

Abstract: Protopanaxadiol (PPD)-type ginsenosides are the main ginsenosides in ginseng (Panax ginseng C. A. Meyer) with potential therapeutic effects on diseases related to intestinal flora imbalance. This study aimed to investigate the in vitro metabolism of protopanaxadiol ginsenosides in human intestinal flora and their effect on the flora. Rapid resolution liquid chromatography coupled with quadruple-time-of-flight mass spectrometry (RRLC-Q-TOF MS) was utilised for the transformation of ginsenoside constituents for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…[71]. The study also highlighted the high diversity and richness of the group with strong conversion ability, particularly in the dominant groups Firmicutes, Bacteriodetes, and Tenericutes [87].…”
Section: Biotransformation By the Human Intestinal Bacteriamentioning
confidence: 74%
“…[71]. The study also highlighted the high diversity and richness of the group with strong conversion ability, particularly in the dominant groups Firmicutes, Bacteriodetes, and Tenericutes [87].…”
Section: Biotransformation By the Human Intestinal Bacteriamentioning
confidence: 74%
“…Ginsenoside Rd Ginsenoside Rd is one of the metabolites of ginsenoside Rb1 in the intestine ( Zhang et al, 2021 ) and has a wide range of biological activities including neuroprotection, improved metabolism, as well as anti-cancer ( Li J. et al, 2022 ). It is reported that ginsenoside Rd inhibits proliferation and drives apoptosis of BC cells ( Kim 2013 ).…”
Section: Anti-breast Cancer Activity Of Ginsenosidesmentioning
confidence: 99%
“…Therefore, the concurrent use of gut microbiota modulators in cancer chemotherapy is considered to be a promising strategy. Many active ingredients in plants have been found to regulate gut microbiota and improve immunity 16–20 . Whether PPD can regulate gut microbiota has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Many active ingredients in plants have been found to regulate gut microbiota and improve immunity. [16][17][18][19][20] Whether PPD can regulate gut microbiota has not been reported.…”
Section: Introductionmentioning
confidence: 99%